Analisis Sektor Potensial Untuk Mendorong Pembangunan Ekonomi Kota Probolinggo Tahun 2014-2019 - Puspitasari, Hayyum; Prayudi Setiawan Prabowo (Universitas Negeri Surabaya, 2025)
This study aims to analyze potential sectors that can encourage economic development in Probolinggo City. The data usedis GRDP data based on constant prices for the period 2014 – 2019. The research method used to analyze is the Location Quotient (LQ), Shift Share and LQ- SS combined analysis. These methods can be used to classify economic sectors into leading sectors, developing sectors, and lagging sectors. By appointing Probolinggo City as the study area and East Java Province as the reference area, using this analysis method it can be seen which sectors are the base sector, non-base sectorand leading sector, and can find out how the economy of Probolinggo City is compared to the reference area. Based on the results of the research analysis, the City of Probolinggo in 2014-2019 is classified as a region that can still develop rapidly, which has ten basic sectors and thirteen leading sectors.